Malacañan Palace : the official illustrated history - Quezon, Manuel L.; Alcazaren, Paulo ;Barns, Jeremy (Manila, Philippines : Studio 5 Pub., 2005)
The genesis of this book was the long interregnum between the late National Artist Nick Joaquin's commission to write a history of Malacanan Palace, and the publication of the book a decade later.
Chapter 1. A Riverside Home Chapter 2. The seat of the first authority Chapter 3. Serving manifest destiny Chapter 4. The Fulcrum of National life Chapter 5. Conscious stewardess Chapter 6. Fount of the new society
Includes bibliographical references (pages 324-326) and index.
Keywords: PHILIPPINES HISTORY